Treaty with the Wyandot, 1850. - United States; Wyandot Tribe ([Getzville, New York] : William S. Hein & Company, 2020)
Articles of a convention concluded in the city of Washington, this first day of April, one thousand eight hundred and fifty, by and between Ardavan S. Loughery, commissioner especially appointed by the President of the United States, and the undersigned head chief and deputies of the Wyandot tribe of Indians, duly authorized and empowered to act for their tribe--
"Treaty Number: NAM000273."
Treaty date: 4/1/1850.
9 Stat. 987
2 Indian Affairs Laws and Treaties (1904) 587
Extracted from: United States. Statutes at large and treaties of the United States of America. Boston : Charles C. Little and James Brown, 1851-1859.
Extracted from: United States. Indian affairs : laws and treaties / compiled and edited by Charles J. Kappler. Washington : Government Printing Office, 1903-1971.
Keywords: Wyandot Tribe -- Treaties; Wyandot Indians -- Government relations; Wyandot Indians -- Legal status, laws, etc; Indians of North America -- Treaties; Treaties